Pengaruh Adopsi Teknologi dan Dukungan Sosial Terhadap Kesejahteraan Petani di Desa Gitgit, Kecamatan Sukasada, Kabupaten Buleleng - Putu Anggi Junistya Putri; Kadek Rai Suwena (Jurnal Pendidikan Ekonomi Undiksha, 2026)
The agricultural sector remains the main pillar of rural livelihoods and plays an important role in supporting household economies. This study aims to examine the effect of technology adoption and social support on the welfare of farmers in Gitgit Village, Sukasada District, Buleleng Regency. This research employs a quantitative approach using multiple linear regression analysis. The population of this study consists of clove and coffee farmers in Gitgit Village, with a sample of 178 respondents selected through purposive sampling. Data were collected using questionnaires that had been tested for validity and reliability. The results indicate that: (1) simultaneously, technology adoption and social support have a positive and significant effect on farmers’ welfare; (2) partially, technology adoption has a positive and significant effect on farmers’ welfare; and (3) partially, social support has a positive and significant effect on farmers’ welfare. The coefficient of determination test shows that technology adoption and social support contribute 75.2 percent to farmers’ welfare, while the remaining percentage is influenced by other factors outside this study